Linking knowledge management, organizational learning and memory - Helder de Jesus Ginja Antunes; Paulo Gonçalves Pinheiro (Journal of Innovation & Knowledge (JIK), 2020)
The objective of this research is to understand the link and evolution between the concepts of knowledge management, organizational learning and memory. Seeking a better clarification of concepts, discussing them in the theoretical field, understanding their evolution in the last decades. A systematic literature review was developed by synthesizing concepts. From two databases, a total of 2511 scientific articles between 1960 and 2017 were analyzed, divided into two studies. Organizational learning is seen as a dynamic process based on knowledge and is translated through various levels of activity. The ability of an organization to use and leverage the knowledge is heavily dependent on its Human Resources, which are effectively who creates, shares and uses that knowledge. Knowledge management is seen as the management of the processes of creation, storage, access, and dissemination of the intellectual resources of an organization. Organizations must consider your main objective as increasing the capacity of individuals and organizational knowledge enhancers. Managers should pay special attention to the more general knowledge associated with the context of the firm, as it supports the introduction of various types of innovation. Knowledge can be encouraged by a set of collaborative practices of HRM. We can consider organizational learning as a process and organizational memory as the corresponding output. Thus, establishing the relationship that the organizational memory is a consequence of organizational learning. Key concepts that can be used in the new future research are summarized, highlighting its application and diagnosis for organizations, fomenting the strategic decision-making.
Keywords: M01; M15; 650; Knowledge management; Organizational learning; Memory; Systematic literature review